Investigações teóricas em compostos de coordenação contendo metais de transição e íons lantanídeos: elaboração de métodos e aplicações em bioinorgânica - Cavalcanti, Higo de Lima Bezerra (2017)
In this work, two problems involving the transition block of the periodic table were addressed: (i) the Mn-N-tetrapyridylporphyrins, which comprise the most efficient catalytic mimics of Superoxide Dismutase enzyme, one of the major responsible for managing the levels of the free radical superoxide (O2•–) in the organism, were studied in the perspective of the determination of their ground spin states by DFT methods. In the other hand, (ii) a new set of parameters for trications ions of Eu, Gd and Tb were obtained and implemented in the semiempirical method RM1, aiming to generate a method that can predict accurately the geometry of complexes containing these lanthanide ions, which are important in diverse technological and biological areas. Regarding (i), geometry optimizations at gas phase were carried out at (U)TPSSh/LANL2DZ/6-311G(d) level for the singlet (LS), triplet (IS) and quintet (HS) states of the porphyrins labeled MnTPPCl, MnT-4-PyP+, MnTM-4-PyP5+ and MnTM-2-PyP5+. Afterwards, 18 combinations of exchange and correlation functionals along with a variety of basis sets were applied to assess the spin state energy ordering of MnTPPCl, complex to which spin state diversity is experimentally known. Following this step, BLYP, PW91, TPSS, TPSSh, OPBE, BLYPD3, TPSSD3 and B97D3 along with 6-31G(d), m6-31G(d) and s6-31G(d) basis sets were assessed, resulting in an energy ordering as follows: HS < IS < LS for all Mn-Nalkylpyridylporphyrins. Every studied effect acted to favor the HS state: dispersion effect of ~2.70 kJ/mol, Hartree-Fock exchange of ~19,50 kJ/mol and entropic corrections of ~10.80 kJ/mol. (ii) a numerous data base containing dozens of Eu(III), Gd(III) and Tb(III) complexes was assembled, followed by a rigorous procedure of simultaneous optimization of the 22 parameters that appear in RM1 model for each lanthanide ion. The new set of parameters allowed the prediction of geometries with unsigned mean errors in the order of 0.05 Å for the distances between the lanthanide and the atoms directly coordinated to it and a mean error of 0.13 Å if all bonds are considered. Besides, a more accurate modeling of bonds such as Ln–C, Ln–S, Ln–Cl and Ln–Br was achieved, in a clear improvement over the existing semiempirical methods.